2014
DOI: 10.1038/srep04253
|View full text |Cite
|
Sign up to set email alerts
|

Shaping a lateralized brain: Asymmetrical light experience modulates access to visual interhemispheric information in pigeons

Abstract: Cerebral asymmetries result from hemispheric specialization and interhemispheric communication pattern that develop in close gene-environment interactions. To gain a deeper understanding of developmental and functional interrelations, we investigated interhemispheric information exchange in pigeons, which possess a lateralized visual system that develops in response to asymmetrical ontogenetic light stimulation. We monocularly trained pigeons with or without embryonic light experience in color discriminations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 47 publications
3
24
0
Order By: Relevance
“…Consequently, left-sided tectofugal lesions result in more severe visual deficits than right-sided ones (G€ unt€ urk€ un and Hahmann, 1999;Valencia-Alfonso et al, 2009). Dark incubation abolishes these anatomical tectofugal asymmetries (Manns and G€ unt€ urk€ un, 1999a(Manns and G€ unt€ urk€ un, , 1999b(Manns and G€ unt€ urk€ un, , 2003 and alters inter-hemispheric transfer (Manns and Rö mling, 2012;Letzner et al, 2014). Thus, lateralized light input before hatch induces both structural and behavioral asymmetries.…”
Section: Avian Asymmetry: From Stimulation Asymmetry To Lateralized Cmentioning
confidence: 99%
“…Consequently, left-sided tectofugal lesions result in more severe visual deficits than right-sided ones (G€ unt€ urk€ un and Hahmann, 1999;Valencia-Alfonso et al, 2009). Dark incubation abolishes these anatomical tectofugal asymmetries (Manns and G€ unt€ urk€ un, 1999a(Manns and G€ unt€ urk€ un, , 1999b(Manns and G€ unt€ urk€ un, , 2003 and alters inter-hemispheric transfer (Manns and Rö mling, 2012;Letzner et al, 2014). Thus, lateralized light input before hatch induces both structural and behavioral asymmetries.…”
Section: Avian Asymmetry: From Stimulation Asymmetry To Lateralized Cmentioning
confidence: 99%
“…The exposure of embryos to light not only enhances development of the right-eye-system in advance of the left-eye-system but also leads to the left hemisphere being able to inhibit the right hemisphere via interhemispheric neural connections [80,81]. Further experiments have shown, in pigeons, that light exposure of the embryo modulates the balance between the hemispheres [82].…”
Section: Development and The Role Of Lightmentioning
confidence: 99%
“…Previous studies indicate that light play a vital role in affecting function and behavior of chickens 4 5 6 7 . Further it has been reported that light manipulation has been an effective measure to improve poultry production 8 9 10 .…”
mentioning
confidence: 99%